Quantitative Easing and Bank Lending - Assenga-Amara, Edgar (2015)
There is a growing body of literature currently analysing the effects of Quantitative easing especially in the wake of the 2008 financial crisis as large asset purchase programmes were implemented in the USA and the UK. Traditionally, the studies analysing the effects of QE have tended to focus on its impact on the financial markets as a whole or on interest rates. However, the manner in which quantitative easing works puts banks at the centre of how they operate. Therefore it is important to understand how quantitative easing works through the bank lending channel of monetary policy. Past papers such as Bowman et al. (2011) and Joyce and Spaltro (2012) have analysed the effects of quantitative easing on bank lending however they have tended to focus more on the direct channel of Quantitative easing through the bank lending channel. This study aims to build upon their work by including other channels under which asset purchase programmes could affect bank lending. We use OLS, Fixed effects and GMM estimators to analyse data. To this end, we seek to find how quantitative easing affect banks through an increase in money supply, changes in the bank’s net interest margins and Z-score. We find slight evidence for the indirect path of Quantitative easing especially through the net interest margin. We can’t conclusively ascertain whether the direct channel worked however.